The Role of Work Engagement and Work Spirit in Enhancing job Performance of Sanitation Workers in Cirebon Regency - Sucipto Sucipto; Asep Gunawan; Hevy Febriyansyah (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the influence of Work Engagement and work spirit on the performance of the